Studies on Costa Rican Vanilloideae : the return of Cleistes rosea and a reaffirmation of Epistephium ellipticum - Karremans Lok, Adam Philip; Chinchilla, Isler F.; Rojas Alvarado, Gustavo (2023)
Subfamily Vanilloideae represents a small fraction of the orchid flora of Costa Rica, and yet our knowledge of this predominantly South American group has significantly increased in the last two decades. Until recently, Vanilloideae was represented in Costa Rica by just two genera: Cleistes and Vanilla, with one and seven species respectively. Today, up to 13 species of Vanilla are shown to occur in the country, we evidence the presence of a second species of Cleistes and confirm the presence of a third genus Vanilloideae in Costa Rica: Epistephium. The rare Cleistes rosea and Epistephium ellipticum are fully illustrated on the basis of Costa Rican materials with Lankester Composite Digital Plates (LCDP). The typification of Cleistes rosea is discussed and a color illustration is provided of C. costaricensis for comparison.
La subfamilia Vanilloideae representa una pequeña fracción de la flora de orquídeas de Costa Rica, y sin embargo, nuestro conocimiento de este grupo predominantemente sudamericano ha aumentado significativamente en las últimas dos décadas. Hasta hace poco, Vanilloideae estaba representada en Costa Rica por solo dos géneros: Cleistes y Vanilla, con una y siete especies respectivamente. Hoy en día, se ha comprobado la presencia de hasta 13 especies de Vanilla en el país, aquí evidenciamos la presencia de una segunda especie de Cleistes y confirmamos la presencia de un tercer género de Vanilloideae en Costa Rica: Epistephium. Las raras Cleistes rosea y Epistephium ellipticum se ilustran completamente con base en materiales costarricenses con Láminas Digitales Compuestas Lankester (LCDP). Se discute la tipificación de Cleistes rosea y se proporciona una ilustración a color de C. costaricensis para su comparación.
Keywords: ORQUIDEAS -- COSTA RICA; ORQUIDEAS -- CLASIFICACION -- COSTA RICA